Representações sociais de professores da educação infantil sobre o desenvolvimento da prática pedagógica em Ciências - Silva, Fernanda Duarte Araújo (2015)
This study aimed to discuss issues related to the work with Science in Childhood Education. The questions that guided this research were: What are the representations of Childhood Education teachers from Uberlândia on the work with Science in this level of education? According to the teachers, what must be considered in that area of knowledge? For these subjects, what are the appropriate methodologies for the work with Science? What are the possibilities and difficulties of addressing this discipline in the routine of Childhood Education? Our objective was to investigate the social representations of teachers of Childhood Education, from Uberlândia, about the work with Science and methodologies that must be contemplated in this area of knowledge. We also seek to identify the representations of the subjects on the possibilities and difficulties of the work with Science in Childhood Education. The theoretical and methodological background utilized was that of Social Representations in Moscoviciana perspective. The research is qualitative, and the questionnaires and interviews were the instruments used for data building. The found representations refer to the fact that the work with Science occur in Childhood Education through the following themes: environment, hygiene and feeding. In its representations, the methodologies employed in the work with Science are: expository and dialogued classes, practical activities and work with educational projects. The main representations found on the positive aspects of the work with Science in Childhood Education were: relation of the subjects with the children routine; awareness for social change; learning that occurs through pleasurable activities; possibility of habit formation; the fact of this area of knowledge contemplate practical activities and experiments. The difficulties of the work with Science in Childhood Education focused on issues related to working conditions, such as lack of teaching materials, difficulties with transport to conduct classes outside of school, lack of spaces for practical activities and/or experimentations, gaps in training to work with this area of knowledge and lack of a good relationship with the school community in general. We hope that this research will contribute to the discussions and productions about the work with Science in Childhood Education, topic that is not commonly investigated in the academic community.